Relationship between body mass index and the development of cranium in Arak newborns (Central Iran) - Dokht Bayat, Parvin; Ghanbari, Ali; Chehreie, Shima (Italian Journal of Anatomy and Embryology, 2010)
Adaptive responses which occur under changing environment enable a species existence during long periods of time. This study aimed at investigating the relationship between body mass index (BMI and characteristic of brain in newborns. This study was undertaken on 1800 healthy live born singletons (822 males and 978 females) routinely delivered at the Gynecology Hospital of Arak Medical Sciences University between 2002 and 2003. Anthropometric data were analyzed by linear regression and regression analysis using SPSS software for Windows (version 15). The results showed that BMI (body mass index) was significantly associated with cerebral index upon adjusting for sex. The strict correlation between BMI and cerebral index suggests that newborn fat deposition may have increased to allow for high myelination in the human brain. The extraordinary fat storage in newborns would be a consequence of the selection for larger brain size in hominid evolution.